Conceptual framework of STEM based on Japanese subject principles - Yata, Chikahiko; Ohtani, Tadashi; Isobe, Masataka (International journal of STEM education, 2020)
Background School education should improve science, technology, engineering, and mathematics (STEM) ability not only in science and mathematics but also in technology and engineering. However, practice and research are being conducted without clear definitions and methods for STEM education. Moreover, the positioning and characteristics of the technology included in each STEM field are unclear. Therefore, it is necessary to propose an appropriate framework for practice of STEM from the viewpoint of technology education. In response to this need, this commentary proposes a conceptual framework for the appropriate practice of STEM education. Results First, we referred to the perspectives and thinking styles of the fields of science, technology, and mathematics in the Japanese curriculum to specify the approach of the education system to each subject included in STEM. Next, to determine the concept of engineering in STEM education, we referred to the definition of engineering presented in Japan, the USA, and the UK. We positioned engineering, which means creating structures, processes, systems, etc., as a practical STEM activity and attempted to relate it to the unique perspectives and thinking styles of mathematics, science, and technology. Conclusion We proposed a conceptual framework for the appropriate practice of STEM education based on the principles of subjects in the Japanese curriculum. The conceptual framework suggests that a means to improve the practice of STEM education is to retain the principles of science, technology, and mathematics in the activity of engineering. It can be inferred that the key point for practicing STEM education is to examine and design the appropriate order and combination of the learning process and activities based on the proposed conceptual framework. Although this framework is theoretical, it can be useful in determining an adequate practice of STEM education and clarifying the relationship between STEM education and technology education.